The Kanhaapproach to Tiger Conservation - Shukla, Rakesh (Indian Forester, 2004)
The tiger is regarded as a highly endangered species in all the tiger range countries of the world. The conservation of the magnificent species has evoked a tremendous response from all over the world. The situation in India is still far from satisfactory. There are only a few wildlife protected areas, which inspire confidence for the reversal of the tiger population to a safer status. Kanha Tiger Reserve is one such, harbouring tbe typical floral and faunal attributes of Central Indian Highlands and a viable population of the tiger, Kanha, with a long conservation history and a succession of dedicated officers and staff, has developed into an excellent institution for conservation of wildlife in general and tiger in particular. Tiger conservation in Kanha Tiger Reserve involves an allround strategy, comprising relocation efforts, protection, build.up of prey base, and the park-people co-operation. The lessons learnt from Kanha also offer general implications for effective tiger conservation for other Tiger Reserves of the country.